ANALISIS KEBERADAAN BAKTERI ENTEROBACTER PADA AIR CUCIAN IKAN LAYANG (DECAPTERUS SPP) DI PASAR MARDIKA DAN PASAR TAGALAYA AMBON - Manusiwa, Gellian Gabriella; Pattipeilohy, Mery; Pelamonia, Alamanda; Mahulette, Ferymon (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Fish sales generally do not prioritize sanitation aspects in Ambon city. This study aims to determine the presence of Enterobacter bacteria and the morphological characteristics of Enterobacter bacteria in the washing water of flying fish (Decapterus spp) at Mardika Market and Tagalaya Market Ambon. Wash water samples were taken at Mardika and Tagalaya Markets in Ambon. Methods: The analysis used the Most Probable Number (MPN) method and biochemical tests (methyl red and citrate tests). Results: The results showed that 6 samples of flying fish washing water at the mardika market and tagalaya market that had been tested were identified as Enterobacter bacteria and based on the morphological characteristics found in the washing water samples of flying fish were pink, smooth edges, wavy, curved, and also not sequential and the elevation was flat and raised. The methyl red and citrate tests were negatife and positive respectively. Conclusion: Flying fish washing water at the Mardika and Tagalaya Markets has been contaminated with Enterobacter bacteria.